Predictor Organizational Citizenship Behavior through the Role of Mediation Organizational Commitment - Ferdi Yansyah; I Ketut R. Sudiarditha; Christian Wiradendi Wolor (International Journal on Advanced Science, Education, and Religion, 2022)
The article aimed of analyzing the effect of perceived organizational support and organizational justice on organizational citizenship behavior through organizational commitment as mediation or intervening. It studied at he Public Sector Institution in Jakarta. The population of this study were 642 employees of Instansi X, consisting of Civil Servants (PNS), TNI soldiers, and members of the National Police, ranging from non-echelon to echelon I/equivalent levels. The sampling technique used non-probability sampling (purposive sampling). The questionnaire was addressed to Instansi X civil servants from non-echelon to echelon III levels. The results of distributing questionnaires obtained a sample of 200 respondents. The research method used a quantitative approach while the data analysis method used descriptive statistical analysis and SEM (Structural Equation Modeling) analysis with the Analysis of Moment Structures (AMOS) version 24 program. The results showed that perceived organizational support and organizational justice had a positive and significant direct effect on organizational citizenship behavior and organizational commitment. The results of this study produce a contribution to the development of literature regarding the effect of perceived organizational support and organizational justice on organizational citizenship behavior through organizational commitment as mediation/intervening, as well as adding theoretical contributions to predictors of the emergence of organizational citizenship behavior of employees in the government sector which are still rarely found. Keywords: Perceived Organizational Support, Organizational Commitment, Organizational Citizenship Behavior